Striatal Activity is Associated with Deficits of Cognitive Control and Aberrant Salience for Patients with Schizophrenia - Ceaser, Alan E.; Barch, Deanna M. (Frontiers in Human Neuroscience, 2016)
A recent meta-analysis has shown that a large dopamine abnormality exists in the striatum when comparing patients with schizophrenia and controls, and this abnormality is thought to contribute to aberrant salience assignment (or a misattribution of relevance to irrelevant stimuli). This abnormality may also disrupt striatal contributions to cognitive control processing. We examined the relationship between striatal involvement in cognition and aberrant salience symptoms using a task of cognitive control that involves updating, interference control, and simple maintenance. The current study included a sample of 22 patients with schizophrenia and 20 healthy controls and used a slow event-related fMRI design. We predicted that 1) aberrant salience symptoms would be greater for patient’s, 2) patients would demonstrate increased errors during interference control trials, given that patients may be inappropriately assigning salience to distracters, and 3) striatal activity during those errors would be correlated with aberrant salience symptoms. We found a trend toward a significant difference between patients and controls on aberrant salience symptoms, and a significant difference between groups on select task conditions. During interference control trials, patients were more likely to inappropriately encode distracters. For patients, both prefrontal and striatal activity was significantly greater when patients inappropriately identified the distracter as correct compared to activity during distracter rejection. During updating, patient prefrontal and striatal activity was significantly lower for incorrect than correct updating trials. Finally, as predicted, for patients the increase of activity during incorrect distracter trials was positively correlated with aberrant salience symptoms, but only for the striatal region. These relationships may have implications for treatments that improve cognitive function and reduce symptom expression.